Brain metastases in patients with EGFR-mutated or ALK-rearranged non-small-cell lung cancers. Issue 1 (April 2015) - Rangachari, Deepa; Yamaguchi, Norihiro; VanderLaan, Paul A.; Folch, Erik; Mahadevan, Anand; Floyd, Scott R.; Uhlmann, Erik J.; Wong, Eric T.; Dahlberg, Suzanne E.; Huberman, Mark S.; Costa, Daniel B.
Highlights Brain metastases are frequent in ALK rearranged lung cancers. Brain metastases are frequent in EGFR mutated lung cancers. ∼25% of patients at diagnosis and half at 3-years of survival have brain metastases.